A compact explicit DC model for short channel Gate-All-Around junctionless MOSFETs. (May 2017) - Lime, François; Ávila-Herrera, Fernando; Cerdeira, Antonio; Iñiguez, Benjamín
Highlights: A DC compact model for the cylindrical GAA MOSFET is proposed. Short channel effects are taken into accounted. The model is explicit with relatively simple equations. Abstract: In this paper we provide solutions to update a long channel model in order to take into account the short channel effects. The presented model is for the junctionless GAA MOSFETs. The resulting model is analytical, explicit and valid for depletion and accumulation regimes, and consists of simple physically based equations, for better understanding of this device, and also easier implementation and better computation speed as a compact model. The agreement with TCAD simulations is very good.